Amino Acid Metabolism in Lupus - Kono, Michihito; Yoshida, Nobuya; Tsokos, George C. (Frontiers in Immunology, 2021)
T cell metabolism is central to cell proliferation, survival, differentiation and aberrations have been linked to the pathophysiology of systemic autoimmune diseases. Besides glycolysis and fatty acid oxidation/synthesis, amino acid metabolism is also crucial in T cell metabolism. It appears that each T cell subset favors a unique metabolic process and that metabolic reprogramming changes cell fate. Here we review the mechanisms whereby amino acid transport and metabolism affects T cell activation, differentiation and function in T cells in the prototype systemic autoimmune disease systemic lupus erythematosus. New insights in amino acid handling by T cells should guide approaches to correct T cell abnormalities and disease pathology.